Comorbidities in situs inversus totalis: A hospital‐based study. Issue 5 (29th January 2020) - Chen, Weicheng; Guo, Zhuoyao; Qian, Liling; Wang, Libo
Abstract: Background and objective: Few studies have assessed the comorbid diseases in situs inversus totalis (SIT) comprehensively. The aim of this study was to provide insight into the spectrum and prevalence of comorbidities in SIT. Methods: Children ≤18 years of age with SIT were enrolled in this retrospective observational study. Situs status and comorbidities were independently confirmed by two physicians, based on review of radiologic, ultrasonic examination, operative records, and case notes. Results: A total of 155 children (median age: 1.24 years; range: 1 day–17.8 years) confirmed to have SIT were recruited between January 2008 and December 2018. Associated conditions were diagnosed in 114 children (73.5%). Among them, 25 children (16.1%) had multiple anomalies affecting two or more organ systems. The most commonly associated conditions were congenital heart defects ( n = 72, 46.5%) followed by primary ciliary dyskinesia ( n = 19, 12.3%), renal disorders ( n = 12, 7.7%), biliary atresia ( n = 7, 4.5%), skeletal dysplasia ( n = 8, 5.2%), and mental retardation ( n = 4, 2.6%). Conclusion: A substantial proportion of children with SIT have comorbidities affecting multiple systems, especially cardiovascular and respiratory abnormalities. Children with SIT warrant careful examination for the presence of congenital and acquired abnormalities.